Microbially Induced Calcium Carbonate Precipitation (MICP) and Its Potential in Bioconcrete: Microbiological and Molecular Concepts - Castro-Alonso, María José; Montañez-Hernandez, Lilia Ernestina; Sanchez-Muñoz, Maria Alejandra; Macias Franco, Mariel Rubi; Narayanasamy, Rajeswari; Balagurusamy, Nagamani (Frontiers in Materials, 2019)
In this review, microbiological and molecular concepts of Microbially induced Calcium Carbonate Precipitation (MICP) and their role in bioconcrete are discussed. MICP is a widespread biochemical process in soils, caves, freshwater, marine sediments and hypersaline habitats. MICP is an outcome of metabolic interactions between diverse microbial communities with organic and/or inorganic compounds present in environment. Some of the major metabolic processes involved in MICP at different levels are urea hydrolysis, denitrification, dissimilatory sulfate reduction and photosynthesis. Currently, MICP directed by urea hydrolysis, denitrification and dissimilatory sulfate reduction has been reported to aid in development of bioconcrete and demonstrated improvement in mechanical and structural properties of concrete. Bioconcrete is a promising sustainable technology in reducing the negative environmental impacts due to CO2 emission from construction sector and as well as in terms of economic benefits by way of promoting self-healing process of the concrete structures. Among the metabolic processes mentioned above, urea hydrolysis is the most applied in concrete repair mechanisms. MICP by urea hydrolysis is induced by a series of reactions driven by urease (Ur) and carbonic anhydrase (CA). Catalytic activity of these two enzymes depends on diverse parameters, which are currently being studied under laboratory conditions to understand the biochemical mechanisms involved and their regulation in microorganisms. It is clearly evident that microbiological and molecular components are essential to improve the process and performance of bioconcrete.